Spiritual Factors of Protecting Youth from the Threat of Popular Culture - Shukurova, Nilufar Khaliyarovna (Researchparks Publishing, 2023)
The article examines the issues of protecting young people in our country from the threats of popular culture, which are becoming a negative evil of today, protecting our children from the dangers of moral culture in public life. It scientifically studies the essence of spiritual reforms in the fight against popular culture, based on the changes taking place in New Uzbekistan.